Matter Density Distributions and Reaction Cross Sections for 8Li and 22N Exotic Nuclei - Abdullah, Suhaib Q.; Abdullah, Ahmed N. (Iraqi Journal of Science, 2022)
The Harmonic Oscillator (HO) and Gaussian (GS) wave functions within the Binary Cluster Model (BCM) were employed to investigate neutron, proton and matter densities of the ground state as well as the elastic proton form factors of one neutron 8Li and 22N halo nuclei. The long tail is a property that is clearly shown in the neutron density. The existence of a long tail in the neutron densities of 8Li and 22N indicates that these nuclei have a neutron halo structure. Moreover, the matter rms radii and the reaction cross section  of these nuclei were calculated using the Glauber model.